Digital Technologies as a Factor in Increasing Services Sales in Tourism Industry - NIMATULAEV, Magomedkhan Magomedovich; SIRBILADZE, Ketevan Kitaevna; TSVETKOVA, Olga Nikolaevna; IVANOVA, Liudmila Ivanovna; SHELYGOV, Aleksandr Vladimirovich (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021, 2021)
The article is devoted to the analysis of digital technologies as a factor in increasing services sales in the tourism industry. It has been established that information and services markets should satisfy the needs of all categories of consumers who want a service. The state should support and promote the development of both conventional services providers that prefer personal communication during the purchase of a service and online travel firms. It has been found that digital technologies also play an important role when marketing functions are carried out by travel companies because they simplify the resolution of difficult tasks in a dynamic and constantly changing business environment. It has been proven that digital technologies can support marketing by providing information required to make marketing decisions and offer new channels for the provision of travel services.